![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
计算(1^2-2^2/1+2)+(2^2-3^2/2+3)+(3^2-4^2/3+4)+.....+2006^2-2007^2/2006+2007
1个回答
展开全部
(1^2-2^2/1+2)+(2^2-3^2/2+3)+(3^2-4^2/3+4)+.....+2006^2-2007^2/2006+2007
=(1+2)(1-2)/(1+2)+(2+3)(2-3)/(2+3)+(3+4)(3-4)/(3+4)+....+(2006+2007)(2006-2007)/(2006+2007)
=(-1)+(-1)+(-1)+....+(-1)
=-2006
=(1+2)(1-2)/(1+2)+(2+3)(2-3)/(2+3)+(3+4)(3-4)/(3+4)+....+(2006+2007)(2006-2007)/(2006+2007)
=(-1)+(-1)+(-1)+....+(-1)
=-2006
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询